Elaboration of a Model of Temporary Cooperation in Tourism’ Destination Promotion A Systematic Literature Review - Maria Garbelli (European Scientific Journal, ESJ, 2020)
The literature considers cooperation as the best way for a region to achieve a competitive advantage in global, digital markets, and as taking a key role in achieving the promotion of a comprehensive, sustainable destination. In recent years, the body of research on cooperation in tourism has grown considerably, listing several opportunities for decreasing competitive pressure among local tourism actors, while gaining the superior advantages of collaboration. At the same time, the literature does not suggest particular models of cooperation for the tourism industry, as most are borrowed from the manufacturing industry, where cooperation seems widely used and further adapted for the tourism domain.Through an in-depth systematic literature review, this paper matches the theories on cooperation in tourism with the concept of temporary cooperation, in order to adapt a model widely considered in several domains, the virtual enterprise (VE), to the peculiarities of the tourism industry. The adaptation is considered according to the particularities of the tourism industry, and especially when cooperation involves local tourism authorities in global turbulent markets. A cycle model consisting of nine-stages life was built, highlighting the main features of a temporary alliance among authorities: the pivotal role of the destination management organization, the relevance of information and communication technologies for the VE’s operability, the short lifetime of the VE, and the destination’s overall promotion.